G341(P) "Very frequent flyers" in A and E and urgent care centres – clinical characteristics of those who attend 9 or more times per annum. (27th April 2016) - Crehan, C; Kugler, B; Boreham, C; Lim, V; Hiles, S; Mackenzie, G; Blair, M
Abstract : Background: Our group has been analysing routine operational data on A and E and UCC attendances with a focus on "frequent flyers" – those who attend 4 or more times per year. Aims: To test the hypothesis that those who repeatedly attend fall into two main groups: chronic long standing illness (CLSI) and those who decide to attend A&E out of choice or preference. To describe the clinical characteristics of a subgroup attending very frequently. Method: Retrospective analysis conducted on routine operational data collected for a large DGH. The data set included collated paediatric attendances to the Urgent care centre and paediatric A+E at the Hospital over a one-year period (01/10/13–30/09/14). A sub-group of those attending nine or more times was analysed. Results: 10641 patients under 5 attended A&E in the time period, 753 attended 4 or more times, 33 attended 9 or more times (over a total of 337 attendances). Of these, 23% required admission and 77% and were discharged. Of the top 33 attenders 15 (45%) had a CLSI, (6, 18% multiple e.g ex-prem, Intraventricular haemorrhage and Chronic lung disease, 9, 27% single e.g. cleft palate). More than half 18 (55%) had no underlying chronic illness. In patients with chronic disease background admission risk was significantly higher Table 1 . (Chi Sq 22.7, p = 0.00002) The most common diagnosis in the top 33 attenders was upper respiratory tract infection, followed by unspecified viral infection, acute bronchiolitis and intestinal infection. The top three diagnoses for the different patient groups are shown in Table 2 . Conclusion: Frequent attenders can be characterised into two different groups, those with chronic underlying conditions and those without. We are exploring options to reduce repeat A&E/UCC attendance by those with chronic illnesses with additional community specialist nurse support and in both groups with parental and GP education particularly targeting the management of respiratory illness.